Introduction - Charles Tatum (Studies in 20th & 21st Century Literature, 2001)
Contemporary cultural critics have theorized the multiple aspects of "location" in many different ways…
Keywords: location; translational location; border; borderlands; Gloria Anzldúa; Homi Bhabha; Gilles Dedeuze; Félix Guatarri; Nestor Garcia Canclini; Edouard Glissant; D. Emily Hicks; Mary Louise Pratt; José David Saldívar; identity; cultural production; culture; chicano/a literature; Argentine literature; Caribbean literature; American Literature